Expert Consensus Statement: Management of Pediatric Persistent Obstructive Sleep Apnea After Adenotonsillectomy. (26th January 2023) - Ishman, Stacey L.; Maturo, Stephen; Schwartz, Seth; McKenna, Margo; Baldassari, Cristina M.; Bergeron, Mathieu; Chernobilsky, Boris; Ehsan, Zarmina; Gagnon, Lisa; Liu, Yi‐Chun Carol; Smith, David F.; Stanley, Jeffrey; et al.
Abstract: Objective: To develop an expert consensus statement regarding persistent pediatric obstructive sleep apnea (OSA) focused on quality improvement and clarification of controversies. Persistent OSA was defined as OSA after adenotonsillectomy or OSA after tonsillectomy when adenoids are not enlarged. Methods: An expert panel of clinicians, nominated by stakeholder organizations, used the published consensus statement methodology from the American Academy of Otolaryngology‐Head and Neck Surgery to develop statements for a target population of children aged 2‐18 years. A medical librarian systematically searched the literature used as a basis for the clinical statements. A modified Delphi method was used to distill expert opinion and compose statements that met a standardized definition of consensus. Duplicate statements were combined prior to the final Delphi survey. Results: After 3 iterative Delphi surveys, 34 statements met the criteria for consensus, while 18 statements did not. The clinical statements were grouped into 7 categories: general, patient assessment, management of patients with obesity, medical management, drug‐induced sleep endoscopy, surgical management, and postoperative care. Conclusion: The panel reached a consensus for 34 statements related to the assessment, management and postoperative care of children with persistent OSA. These statements can be used to establish care algorithms, improve clinical care, and identify areas that would benefit from future research.